2005
DOI: 10.1017/cbo9780511490323
|View full text |Cite
|
Sign up to set email alerts
|

Social Traps and the Problem of Trust

Abstract: A 'social trap' is a situation where individuals, groups or organisations are unable to cooperate owing to mutual distrust and lack of social capital, even where cooperation would benefit all. Examples include civil strife, pervasive corruption, ethnic discrimination, depletion of natural resources and misuse of social insurance systems. Much has been written attempting to explain the problem, but rather less material is available on how to escape it. In this book, Bo Rothstein explores how social capital and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
351
0
30

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 531 publications
(399 citation statements)
references
References 142 publications
6
351
0
30
Order By: Relevance
“…In empirical research, studies have shown that social capital, defined as generalized trust in other people and access to social networks, is determined by the quality of the governmental institutions rather than the other way around (Delhey and Newton 2005;Rothstein 2005). Moreover, it has been demonstrated that democracy in terms of the equal access to power (political equality) is not sufficient for good governance.…”
Section: Post-decision Functions and Normative Political Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In empirical research, studies have shown that social capital, defined as generalized trust in other people and access to social networks, is determined by the quality of the governmental institutions rather than the other way around (Delhey and Newton 2005;Rothstein 2005). Moreover, it has been demonstrated that democracy in terms of the equal access to power (political equality) is not sufficient for good governance.…”
Section: Post-decision Functions and Normative Political Principlesmentioning
confidence: 99%
“…Yet, output impartiality is shown to be one of the most important factors for explaining good governance (Rothstein andTeorell 2008, 2012). Empirical scholars have found that impartial and effective executive institutions matter more than representational institutions for how satisfied citizens are with their democratic government (Dahlberg and Holmberg 2014).…”
Section: Post-decision Functions and Normative Political Principlesmentioning
confidence: 99%
“…Personal trust towards relatives and friends may still be important in every day personal interactions, but society is no longer based on personal relations held together by personal trust. Generalized or extended trust among strangers is the adequate form of trust in a depersonalized society of strangers (Uslaner, 2002;Rothstein, 2005;Reiser, 1999). Some authors present this form of trust as moralistic since it is not based primarily on personal experiences, but can be considered as "the belief that others share your fundamental moral values and therefore should be treated as you would wish to be treated by them" (Uslaner, 2002: 18).…”
Section: IVmentioning
confidence: 99%
“…Persson, Rothstein & Teorell 2012). The same logic undergirds Acemoglu and Robinson's (2012) This leads to an even more difficult problem that has been labeled as a second-order collective action problem (Lichbach 1997;Ostrom 1998;Rothstein 2005). "All" the agents may well understand that they would stand to gain from establishing inclusive political and economic institutions, but they have little reason to cooperate unless they trust that most other agents would not defect in the very process of creating the institutions meant to facilitate cooperative behavior.…”
mentioning
confidence: 90%